Педагогик фаолиятда ўқитувчининг ўз устида ишлаш фаолиятини шакллантиришнинг ижтимоий-психологик хусусиятлари (SCIENCE and SOCIETY, 2024)
This article is devoted to the topic of Socio-psychological problems of raising children in the conditions of pedagogi- cal activity. Thus, Mao Zedong’s pedagogical activity is based on such issues as psychological foundations, social psychological deter- minants, psychological motives, tolerance and empathic motives.